Developing Critical Thinking Skills of Students in Mathematics Learning - Firdaus Firdaus; Ismail Kailani; Md. Nor Bin Bakar; Bakry Bakry (Intelektual Pustaka Media Utama, 2015)
Critical thinking skills should be owned by students. Therefore, schools should be responsible to develop and evaluate critical thinking skills through teaching and learning process in schools. This study aims to identify the effects of mathematical learning modules based on problem-based learning to critical thinking skills at secondary school students in District of Bone. Assessment of critical thinking skills in mathematical problem solving non-routine includes three parts; the identification and interpretation of information, information analysis, and evaluate of evidence and arguments. This study involved a total of 68 students grade 12 science state secondary school (SMAN) in Bone District of South Sulawesi, Indonesia in academic year 2014-2015. The sample consists of 38 students in the city and 30 rural students. The design of the study was quasi experimental one group pretest-posttest. The data was analysed using the inferential t-test with SPSS 20.0 for windows. The study found that there are effects of the use of mathematical learning module based PBL to enhance the ability of critical thinking skills in mathematics students in all three components, namely, identifying and interpreting information, information analysis, and evaluate of evidence and argument.